2011
DOI: 10.1111/j.1749-6632.2011.06207.x
|View full text |Cite
|
Sign up to set email alerts
|

Everyday problem solving across the adult life span: solution diversity and efficacy

Abstract: Everyday problem solving involves examining the solutions that individuals generate when faced with problems that take place in their everyday experiences. Problems can range from medication adherence and meal preparation to disagreeing with a physician over a recommended medical procedure or compromising with extended family members over where to host Thanksgiving dinner. Across the life span, research has demonstrated divergent patterns of change in performance based on the type of everyday problems used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 82 publications
(185 reference statements)
3
31
0
4
Order By: Relevance
“…We must not forget that wisdom increases, and they have accumulated more experience, which helps them to make good decisions. However, we have to consider that as we age decreases the number of the identified alternatives, but increases the number of effective alternatives (Mienaltowski, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…We must not forget that wisdom increases, and they have accumulated more experience, which helps them to make good decisions. However, we have to consider that as we age decreases the number of the identified alternatives, but increases the number of effective alternatives (Mienaltowski, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The assumption that greater age predicates lower performance with ICTs has been increasingly questioned in academic research. Critics contend that the advantages of youth are an artifact of experimental designs, which rely on structured problems such as playing a computer game or physically manipulating interface components as tasks (Mienaltowski 2011). For example, under laboratory conditions, Myerson et al (2007) observed that younger subjects could identify items as belonging to a common category much faster than older subjects.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Buna karşın, Heidrich ve Denney'in (1994) benzer yaş aralığındaki (18-81) bireylerde yürüttüğü bir araştırmada sosyal problem çözme performansının diğer yaş dönemlerine göre 30 ve 40'lılı yıllarda daha yüksek olduğu belirtilse de yaşın sosyal problem çözme performansını yordamadığının altı çizilmiştir. Günlük problem çözme performansının genç yetişkinlikten orta yaş döneminin sonlarına kadar arttığını ve sonraki dönemlerde ilerleyen yaşla birlikte azaldığını öne süren araştırmacılar bu bulguların nedeni olarak günlük yaşam deneyimlerinden kaynaklanan kazançların gittikçe artmasına ve yapısal veya nörolojik düşüşlerin bu gelişimsel dönemler içerisinde görece az olmasına bağlamışlardır (Mienaltowski 2011). Bir diğer ifade ile orta yetişkin-lik döneminde yer alan bireylerde günlük problem çözme performanısının en yüksek düzeyde olmasının nedeni bilişsel kapasitelerin nispeten korunması ve deneyimin birikimli olarak artmasıdır.…”
Section: Problem çöZme Performansında Yaşa Bağlı Değişimunclassified
“…Bu nedenle, bir problem karşısında üretilen stratejinin türü ile birlikte o stratejinin seçilmesinde etkili olan faktörleri ve problemin bağlamını da incelemek önemlidir. Problem çözme performansında yaşa bağlı düşüş olmadığını öne süren araş-tırmacılar ise çoğunlukla, çözüm akıcılığı (bir problem karşısında üretilen güvenli ve etkili çözümlerin sayısı) ve problem çözme etkinliğinin operasyonel tanımındaki farklı-lıklara odaklanmışlardır (Mienaltowski 2011). Nitekim bu araştırmacılara göre, günlük problem çözme performansında kullanılan yöntemler ve bunların değerlendirilmesi, genellikle üretilen çözümlerin kalitesini ve işlevselliğini hesaba katmamaktadır.…”
Section: Problem çöZme Performansında Yaşa Bağlı Değişimunclassified